Lead release to potable water during the Flint, Michigan water crisis as revealed by routine biosolids monitoring data. (1st September 2019) - Roy, Siddhartha; Tang, Min; Edwards, Marc A.
Abstract: Routine biosolids monitoring data provides an independent and comprehensive means to estimate water lead release pre-, during and post-Flint Water Crisis (FWC). The mass of potable plumbing-related metals (i.e., lead, cadmium, copper, nickel and zinc) in sewage biosolids strongly correlated with one another during the FWC ( p  < 0.05). A simple parametric regression model based on 90 th percentile potable water lead measurements (WLL90) from five city-wide citizen science sampling efforts August 2015–August 2017 was strongly correlated to corresponding monthly lead mass in biosolids [Biosolids-Pb (kg) = 0.483 x WLL90 (μg/L) + 1.79; R 2  = 0.86, p  < 0.05]. Although total biosolids lead increased just 14% during the 18 months of the FWC versus the comparable time pre-FWC, 76% of that increase occurred in July–September 2014, and the corresponding percentage of Flint children under 6 years with elevated blood lead ≥ 5 μg/dL (i.e., %EBL5) doubling from 3.45% to 6.61% in those same three months versus 2013 ( p  < 0.05). %EBL5 was not statistically higher during the remaining months of the FWC compared to pre-FWC or post-FWC. As expected, lead in biosolids during the FWC, when orthophosphate was not added, was moderately correlated with water temperature (R 2  = 0.30, p  < 0.05), but not at other times pre- and post-FWC when orthophosphate was present. Tripling the orthophosphate dose post-FWC versus pre-FWC and some lead pipe removal, decreased lead in biosolids (and %EBL5) to historic lows (2016–2017 vs. 2012–2013; p  < 0.05), supporting the effectiveness of these public health interventions in reducing childhood water lead exposure. Highlights: Lead in biosolids and in water strongly correlate during the 18 months of Flint Water Crisis (FWC). Both lead in biosolids and incidence of elevated blood lead in children spiked in Summer 2014, immediately after the switch to Flint River water. Lead in biosolids and incidence of elevated blood lead in children were not significantly higher in remaining months on Flint River water. The worst childhood lead exposure occurred in 2011, unrelated to the FWC. Biosolids monitoring can provide insights to lead corrosion control effectiveness.